1995
DOI: 10.1093/oxfordjournals.aje.a117562
|View full text |Cite
|
Sign up to set email alerts
|

Social Class and Cancer Patient Survival in Finland

Abstract: The effect of social class on survival was assessed in a cohort of cancer patients identified from the nationwide population-based Finnish Cancer Registry. The cohort consisted of all reported cases of the 12 most common types of cancer occurring in Finland between 1971 and 1985 among persons born in 1906-1945 (n = 106,661). Social class information based on occupation was obtained individually for each patient from the population census of 1970. Both observed and corrected (i.e., cause of death-specific) 5-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 0 publications
7
71
1
Order By: Relevance
“…If all death certificates were based on pathological diagnoses the social class gradient in cancer mortality would be slightly steeper. A smaller proportion of microscopically confirmed diagnosis among lower social classes has also been reported elsewhere (Auvinen et al, 1995).…”
Section: Causal Explanations General Explanation -Mortality From Othesupporting
confidence: 58%
See 4 more Smart Citations
“…If all death certificates were based on pathological diagnoses the social class gradient in cancer mortality would be slightly steeper. A smaller proportion of microscopically confirmed diagnosis among lower social classes has also been reported elsewhere (Auvinen et al, 1995).…”
Section: Causal Explanations General Explanation -Mortality From Othesupporting
confidence: 58%
“…No clear social class differences were observed either before or after adjustment for histological type (squamous cell versus others) among lung cancer patients in the study by Stavraky et al (1987). Auvinen et al (1995) reported effect modification by cell type in lung cancer and leukaemia among men in their study based on more than 100 000 cancer patients. Social class differences were not observed among all patients, but they were confined to non-small-cell lung cancer and acute leukaemia.…”
Section: Specific Explanatory Factorsmentioning
confidence: 75%
See 3 more Smart Citations